The Correlation of the duration of breastfeeding to the nutritional status of infants aged 6 months - Rosalinna, Rosalinna; Paryono, Paryono; srimulati, triwik; Kurniarum, Ari; Siswiyanti, Siswiyanti (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Lack of nutrition at the beginning of life can cause growth failure. One way to increase nutrition is to provide exclusive breastfeeding to infants up to the age of 6 months. The study was conducted to evaluate the length of breastfeeding in infants at the Joton Village, Jogonalan district, Klaten Regency, assessed their nutritional status based on weight and length of the body, as well as analyzing the relationship between the length of breastfeeding and nutritional status at the age of 6 months. This study uses quantitative methods with cross-sectional designs and samples of 55 babies aged 6 months in Februrari until April 2023, chosen by Accidental Sampling method. The results show It was found that there was a relationship between the duration of breastfeeding and nutritional status in body weight/age, body weight/body length and body length/age (p value 0.000). The highest correlation coefficient results occurred in the nutritional status of body length according to age (cc 0.656) which showed a strong correlation